Pengaruh Pertumbuhan Ekonomi, Tingkat Pendidikan, Upah Minimum, Jumlah Penduduk, dan Belanja Modal Terhadap Penyerapan Tenaga Kerja di Provinsi Kalimantan Selatan Tahun 2013-2022 - Hidayah, Astri; Sa'roni, Chairul (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
The research was conducted to test and analyze the influence of economic growth, education level, minimum wage, population and capital expenditure. With secondary data that is descriptive quantitative. The analysis technique used is panel data regression which is a combination of time series data from 2013 - 2022 and cross section data of 13 districts / cities in South Kalimantan Province which are processed using Eviews-12. The results showed that economic growth, education level, minimum wage, population and capital expenditure affect labor absorption simultaneously. Economic growth, education level and capital expenditure have no effect, and minimum wage and population have a significant positive effect on the absorption of Regency / City labor in South Kalimantan Province in 2013 – 2022. Minimum wage is the most dominant factor affecting.